TechOne. Automotive electricity and electronics - Santini, Al (Thomson/Delmar Learning, 2004)
How things work, why we test objects as we do, and what the test instruments tell us are all part of the foundation for this new book on automotive electricity and electronics. Completely up-to-date coverage emphasizes the fundamentals of electronics, setting the stage for smooth progression through more advanced topics such as batteries, starting and charging systems, ignitions, and electrical accessories. Testing is accomplished with common shop tools as well as highly technical equipment. Each chapter is written in a clear and concise fashion that is easy to follow, with current J1930 terminology incorporated throughout